2022
DOI: 10.3390/bs12110452
|View full text |Cite
|
Sign up to set email alerts
|

Examining Nurses’ Vengeful Behaviors: The Effects of Toxic Leadership and Psychological Well-Being

Abstract: Toxic leadership is becoming increasingly common in healthcare organizations and there is strong need for studies focusing on organizational factors that can trigger revenge. Additionally, how psychological well-being functions in shielding against toxicity has not been adequately studied. Hence, this study aims to examine the relationship between toxic leadership and vengeful behaviors of nurses, along with the contingency of psychological well-being on the relationship during the COVID-19 pandemic. In this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Psychological well-being of employees contributes great to the performance of employees and has fruitful results for employees and organizations on the whole [ 15 , 29 ]. But dilemma in current scenario for organizations is the prevalence of negative events at the workplaces that reduce the psychological capital, emotional intelligence and psychological well-being of the employees [ 56 , 57 ].…”
Section: Literature Review Proposed Hypothesis and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological well-being of employees contributes great to the performance of employees and has fruitful results for employees and organizations on the whole [ 15 , 29 ]. But dilemma in current scenario for organizations is the prevalence of negative events at the workplaces that reduce the psychological capital, emotional intelligence and psychological well-being of the employees [ 56 , 57 ].…”
Section: Literature Review Proposed Hypothesis and Frameworkmentioning
confidence: 99%
“…According to Ref. [ 29 ], destructive leaders like toxic, abusive, and despotic leaders can increase the emotional exhaustion among employees and affect their well-being badly. Hence, the performance and job satisfaction among employees are found very low and negative.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found a significant and positive association between toxic leadership, vengeful behavior and deviant behavior. These studies suggest that working under a toxic leader may result in an increase in vengeful (Koç et al, 2022) and deviant behavior in nurses (Khaled Abd El-Aziz Zaki and Samir Abd El-Aziz Elsaiad, 2021). Two studies reported a significant increase in silence behavior in nurses who perceived their nurse managers as toxic (Abdelaliem and Abou Zeid, 2023;Reyhanoglu and Akin, 2022).…”
Section: Major Findings Toxic Leadership Outcomesmentioning
confidence: 99%
“…Therefore, toxic leadership could also negatively influence patient safety outcomes. Evidently, studies that examine mechanisms by which toxic leaders influence outcomes in the nursing workforce remained under research, with only six studies found (Abdelaliem and Abou Zeid, 2023;Bakkal et al, 2019;Budal and Erdal, 2022;Erdal and Budak, 2021;Koç et al, 2022;Reyhanoglu and Akin, 2022). Finally, as the samples from all but three studies (Labrague, 2021a(Labrague, , 2021bLabrague et al, 2020aLabrague et al, , 2020bOfei et al, 2022) were derived from a single site, future studies should consider multi-site data collection to further increase the reliability and validity of the results.…”
Section: Implications For Leadership Researchmentioning
confidence: 99%
See 1 more Smart Citation